The effect of proton ordering in thermal conductivity of clathrate tetrahydrofuran hydrate - Krivchikov, A.I.; Romantsova, O.O.; Korolyuk, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The effect of proton ordering in tetrahydrofuran hydrate has been detected using a technique based on measurement of thermal conductivity. The thermal conductivity of tetrahydrofuran hydrate was measured by the steady-state potentiometric method in an interval of 2–150 K. Two regimes were selected to observe the effect: (i) slow cooling of the hydrate sample and (ii) doping the hydrate with a small quantity of KOH alkali to a concentration of 10-4. Proton ordering affects the temperature dependence of the thermal conductivitychanging its glass-like behavior to crystal-like below 150 K. The phonon maximum that appears in the temperature dependence of the thermal conductivity at T = 17 K is attributed to the cooperative process of local proton ordering stimulated by orientational and ionic defects.